Amelioration of Ultrasonic Transducer to Study CuO Doped Thin Films - BARAKAT, Mirham Abdallah Youssef (Archives of Acoustics, 2018)
Ultrasonic pulse echo technique was used to study cupric oxide (CuO) thin films. CuO thin films were prepared using sol gel technique. They were doped with Lithium (Li) (1%, 2% and 4%). Thin films’ thickness (d) and band gap energy (Eg) were measured. In addition, elastic moduli (longitudinal (L), shear (G), bulk (K) and Young’s (E)) and Poisson’s ratio (v) were determined to estimate the microstructure properties of the prepared films. The study ameliorated the used transducers to overcome their dead zone and beam scattering; wedges were developed. The results showed the effectiveness of these wedges. They enhanced transducers’ sensitivity by changing the dead zone, beam diameter, beam directivity and waves’ transmission. Also, the study noted that Li doping caused the improvement of CuO thin films to be more useful in solar cell fabrication. Li-CuO thin films had narrower band gap. Thus, they acquired a high quantum yield for the excited carriers; also they gained more efficiency to absorb solar light.